POLITICAL RISK FACTORS AFFECTING THE ECONOMY OF THAILAND - Chotiwetsin, Phakin (Asian Political Science Review, 2023)
The objective of this paper was to study the problems, relationships, approaches for the prevention and problem solution political risk factors affecting the economy of Thailand. The research results revealed that the problems of political risk factors and their impact on the economy of Thailand were entirely at the high level. The relationship of political risk factors affecting the economy of Thailand was found to be positively correlated with the statistical significance at .01 level. The approaches in preventing and solving political risks affecting the economy of Thailand were to reduce the creation of political division, to focus on building attitudes, beliefs, and good political culture for people with the measures to reduce gathering and political movement.